DEVELOPMENT OF ELECTRIC CUSTOMER RELATIONSHIP MANAGEMENT FOR ACCELERATION OF CLAIM SERVICES AND COMPLETION FOR CUSTOMER COMPLAINTS IN LIFE INSURANCE COMPANY - Riri Fajriah; Nia Rahma Kurnianda (IJISCS (International Journal of Information System and Computer Science), 2019)
Implementation of e-Customer Relationship Management (e-CRM) in financial services industry will give influence to increase customer loyalty. One indicator of this is the development of features in the e-CRM application that make access easy for customers. However, the development of the e-CRM model is generally applied to the banking sector, while customer service needs in other financial services sectors such as insurance company are equally important. One of the main problems in life insurance companies is the measurement of claims service level agreement. In this research we intend to design an e-CRM application that can facilitate the management of complaints and claims reports in a life insurance company more effectively. The e-CRM application can also facilitate measurement of customer service staff performance in serving customers. In this research we applied the Rapid Application Development (RAD) method for development e-CRM application. The results of this research are development of e-CRM application, complaint management and supporting daily operational of customer care staff in a life insurance company.